Growth of juvenile Piaractus brachypomus fed diets containing different profiles of essential amino acids - Vásquez‑Torres, Wálter; Arias-Castellanos, José Alfredo (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to determine the effect of diets with different profiles of essential amino acids (EAA) on nutrient use efficiency and growth of juvenile pirapitinga (Piaractus brachypomus). Casein and gelatin were used as protein sources, and nine diets were formulated with casein concentration between 0 and 35%, with 4.4% increments and concomitant reduction of gelatin proportion. The amino acid profile of casein, gelatin, and tissue samples from the whole body of juvenile pirapitinga was determined. Dietary levels of casein showed a positive quadratic effect on zootechnical variables. The chemical score between the amino acid profile of body protein and the profile of experimental diets showed that in diets with 31.6 and 35% casein, arginine content becomes limiting. The profile of body amino acids of pirapitinga was similar to the pattern described for teleosts. The amino acid profile obtained with the mixture of casein and gelatin at the ratio of 8:1 is close to the one required for growth of juvenile Piaractus brachypomus.